Implementasi Metode Simple Additive Weighting (Saw) Dalam Sistem Pendukung Keputusan Pemilihan Jenis Smartphone Berbasis Web - Wasilah Wasilah; T. Yudi Hadiwandra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
A smartphone is a breakthrough of mobile devices that designed to make communication easier. The increasing number of sophisticated features on the smartphone allows users to do many things, such as making video calls, online shopping, and even making real-time direct transactions by only using a smartphone. When consumers are going to purchase a smartphone, they are faced with lots of available features so that consumers hardly decided which smartphone suits their needs. As a result, consumers must conduct one by one surveys regarding the smartphone that they are going to buy. According to the reasons, the decision support system in choosing a smartphone through the Simple Additive Weighting (SAW) method can help consumers to select their desirable smartphone without conducting one by one surveys. This system is built using Codelgniter Framework and MySQL database. The system was tested using the usability testing method and the accuracy method by comparing manual calculations with the existing calculations in the system. Based on the test results, it can be concluded that the system is proven to be accurate and feasible to use in assisting users in making smartphone selections. Keywords: decision support system, saw, web, smartphone.